2017
DOI: 10.1021/acs.jpcc.7b02484
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Photoenergy Storage and Photocatalysis Using Polyoxometallates Coupled with a Ru Complex

Abstract: Polyoxometallates (POMs) have been attracting much attention as homogeneous molecular catalysts because of their excellent photocatalytic activities. However, the poor sensitivities of POMs to visible light limit their utilization of solar energy. Here, we studied photoinduced electron transfer (PET) from a Ru complex to POMs such as SiW10O36 8–, W10O32 4–, SiW12O40 4–, and PMo12O40 3– to use them for photoenergy storage and photocatalysis driven by visible light. A hydrophobic Ru complex ([Ru­(nbpy)3]2+; nbpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…To investigate the influence of solvents upon the reaction a series of solvents were examined in the reaction condition and it was observed that solubility of aryldiazonium salt strongly influences product formation. In solvents which the diazonium salts are completely dissolved ([Ru(nbpy) 3 ](PF 6 ) 2 ) complex ( [a] Redox potentials [17] ). 1, entries 1 and 4), the reactions take place with better yields while the reactions took place with lower yields in less soluble solvents such as EtOAc, THF and DCM (Table 1, entries 6,7 and 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the influence of solvents upon the reaction a series of solvents were examined in the reaction condition and it was observed that solubility of aryldiazonium salt strongly influences product formation. In solvents which the diazonium salts are completely dissolved ([Ru(nbpy) 3 ](PF 6 ) 2 ) complex ( [a] Redox potentials [17] ). 1, entries 1 and 4), the reactions take place with better yields while the reactions took place with lower yields in less soluble solvents such as EtOAc, THF and DCM (Table 1, entries 6,7 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…The high electron donating capability of alkyl long chains of nbpy made the LUMO in [Ru(nbpy) 3 ] 2 + more negative because of enhanced electron density of π-conjugated molecules. [17] Although this amphiphilic polypyridyl ruthenium complex has been used as solar water disinfection, [18] photoinduced electron transfer reaction, [19] photoenergy storage [17] and water sensing, [20] to the best of our knowledge it has not been employed as a photocatalyst in traditional organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…It was also revealed that exposing visible light to narrow-band-gap QDs can lead to the injection of photoexcited electrons into POMs to produce one-electron reduced POMs (POM − ). 37 In this study, CsPbBr 3 QDs were coated with TiO 2 prior to coupling with POMs. PL emission modulation was attempted by injecting photoexcited electrons from QDs into POMs through the ntype TiO 2 layer under visible-light irradiation.…”
Section: ■ Introductionmentioning
confidence: 87%
“…We have previously reported efficient electron transfer from QDs such as CuInS 2 and SnO 2 to POMs under UV/visible-light irradiation, leading to effective PL quenching of QDs. It was also revealed that exposing visible light to narrow-band-gap QDs can lead to the injection of photoexcited electrons into POMs to produce one-electron reduced POMs (POM – ) . In this study, CsPbBr 3 QDs were coated with TiO 2 prior to coupling with POMs.…”
Section: Introductionmentioning
confidence: 97%
“…29 The unique properties of POMs, such as structural persistence, strong electron acceptance, reversible redox characteristics, adjustable band structure, environmental friendliness, easy preparation and low-cost, make it become a novel and important potential material for various battery (cell) fields. At present, the review on the research progress of POMs-based materials is mainly focused on the catalytic water oxidation, 37 photocatalysis, 38 supercapacitors and the photoelectric properties of POMs-based films, 39,40 but the application in the third generation of solar cells is rarely summarized or not updated in time. Based on our research work and combined with the latest literature survey, this paper reviews the research status and progress of POMs in the application of the third generation of solar cells and expects the utilization prospects of POMs, hoping to provide some valuable information for the basic research and practical application of related fields.…”
Section: Introductionmentioning
confidence: 99%